Pendampingan Penyusunan Laporan Keuangan dan Penentuan Biaya Serta Promosi UPPKS Asri Sudagaran Chrisma - Harjanti, MG. Fitria; Gunaasih, Sang Ayu Putu Piastini (Jurnal Atma Inovasia, 2023)
This activity service aims to increase knowledge and practice of preparing financial reports, determining costs, and promoting UPPKS Asri Sudagaran partners. UPPKS Asri Sudagaran is a micro business that sells frozen food products located at Sudagaran TR III/1038 Tegalrejo, Yogyakarta City. The service method includes mentoring and mentoring, which is divided into several stages: the planning stage, the implementation stage, process evaluation, and the preparation of financial report preparation modules. After the mentoring process, partners are expected to be able to independently prepare financial reports by existing standards so that they can determine costs based on production costs. In addition, the activities in this service are also expected to provide an in-depth understanding of online promotional media so that it can expand the market share of the frozen food products it produces.